$\dfrac{x}{y+z+t}=\dfrac{y}{z+t+x}=\dfrac{z}{t+x+y}=\dfrac{t}{x+y+z}$
$\rightarrow \dfrac{x}{y+z+t}+1=\dfrac{y}{z+t+x}+1=\dfrac{z}{t+x+y}+1=\dfrac{t}{x+y+z}+1$
$\rightarrow \dfrac{x+y+z+t}{y+z+t}=\dfrac{x+y+z+t}{z+t+x}= \dfrac{x+y+z+t}{t+x+y} =\dfrac{x+y+z+t}{x+y+z}$
Xét $x+y+z+t \neq 0$ thì
$y+z+t=z+t+x=t+x+y=x+y+z$
Dễ suy ra
$x=y=z=t$
Vậy ta có $P=\dfrac{x+y}{z+t}+\dfrac{y+z}{x+t}+\dfrac{z+t}{x+y}+\dfrac{t+x}{y+z}=1+1+1+1=4$
Xét $x+y+z+t=0$ thì
$x+y=-(z+t) \\ y+z=-(x+t) \\ z+t=-(x+y) \\ t+x=-(y+z)$
$\rightarrow P=\dfrac{x+y}{z+t}+\dfrac{y+z}{x+t}+\dfrac{z+t}{x+y}+\dfrac{t+x}{y+z}=(-1)+(-1)+(-1)+(-1)=-4$
Vậy $P \in \{ 4;-4 \}$